2022
DOI: 10.1538/expanim.21-0154
|View full text |Cite
|
Sign up to set email alerts
|

MRI metrics at the epicenter of spinal cord injury are correlated with the stepping process in rhesus monkeys

Abstract: Clinical evaluations of long-term outcomes in the early-stage spinal cord injury (SCI) focus on macroscopic motor performance and are limited in their prognostic precision. This study was designed to investigate the sensitivity of the magnetic resonance imaging (MRI) indexes to the data-driven gait process after SCI. Ten adult female rhesus monkeys were subjected to thoracic SCI. Kinematics-based gait examinations were performed at 1 (early stage) and 12 (chronic stage) months post-SCI. The proportion of stepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[ 32 , 33 ] Patients with SCI can experience a variety of complications, which has adverse effects on their cure and process of rehabilitation. [ 34 ] Therefore, active prevention and treatment of complications are important for the rehabilitation of SCI. This study showed that the RMI, BI, and BBS scores of patients receiving comprehensive strengthening function interventions were significantly higher than those of patients in the general care group, indicating that the neurological and motor function recovery of patients who received the comprehensive intensive functional intervention was significant, which is consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 , 33 ] Patients with SCI can experience a variety of complications, which has adverse effects on their cure and process of rehabilitation. [ 34 ] Therefore, active prevention and treatment of complications are important for the rehabilitation of SCI. This study showed that the RMI, BI, and BBS scores of patients receiving comprehensive strengthening function interventions were significantly higher than those of patients in the general care group, indicating that the neurological and motor function recovery of patients who received the comprehensive intensive functional intervention was significant, which is consistent with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies using animal models, from a rehabilitation perspective, have shown that primates (monkeys and humans) can achieve significantly better locomotor recovery than rodents after unilateral SCIs through a different circuit. Structural reorganization, such as synaptic remodeling, axonal dendritic growth, and circuit reorganization in the supralesional and sublesional spinal cord, can restore function after an injury [82][83][84].To understand the effects of brain plasticity after SCIs from a functional point of view, scales such as the Functional Index Measure [85] and more recent and diagnosis-specific measures such as the Spinal Cord Independence Measure, which fit well with the overall assessment of patient functionality, can be used [86,87]. Additionally, various analyses on different potentials have been developed to investigate how different types of neural signals are transmitted through the same pathway (including motor control) in SCIs.…”
Section: Introductionmentioning
confidence: 99%